Enhancing Science Learning through the Development of Animation Video Media Based on Bruner's Cognitive Theory Using Canva for Students - Eliza Novita; Abna Hidayati; Darmansyah Darmansyah; Ridwan Ridwan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop animated video learning media based on Bruner’s cognitive theory to enhance the science learning process of third-grade students at SDN 18 Koto Tinggi, focusing on the topics of energy sources and energy transformations. Animated videos are used to present abstract concepts through clear visual representations, enabling learning activities that are more engaging and interactive for students. The study applied a research and development approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation, to ensure that the developed media is valid, practical, and effective. The validity of the media was examined through expert validation involving media experts, content experts, and language experts, and the results indicated that the media was highly feasible and appropriate for achieving the intended learning objectives. Effectiveness testing was conducted using pre-test and post-test instruments, which showed a significant improvement in students’ learning outcomes with an N-Gain score of 0.71. In addition, student and teacher responses demonstrated that the animated video media was very practical, easy to use, attractive, and effective when implemented in classroom learning. Overall, this study contributes to literature on technology-based learning media in Indonesia and supports animated videos for elementary science